The effect of using technology as a routine activity in increasing crime rates - Alamiri, Amina Ibrahim; Alomosh, Ahmed Falah (Al-Adab Journal, 2022)
This study seeks to realize the relationship between the use of technology as a routine activity and the increase in crime rates.The importance of the study is that despite the efforts made by governments and media roles in alerting and warning of the negatives and risks of technology, there is a rise in crime rates due to the lack of expertise needed to deal with this virtual world, so it is necessary to avoid the damages and social, security and economic risks, caused by Using technology as a routine activity without awareness and lack of expertise to deal with it or at least limit its effects. The problem of the study was that the high crime rates, depending on the use of technology, will have a negative impact on the social, economic, and cultural level on the individual and society, and that the victim in most technology-related crimes has a significant role no less than the role of the offender in completing the crime.The results of this study showed that most victims of the use of technology had a role in what happened to them. If a perpetrator and a victim were found in a place and time with the absence of control, the crime occurs according to the theory of routine activities, and on the other hand, we find that the conformity of the hypotheses of lifestyle theory confirmed the role of the victim in the occurrence of the crime.The proposals and recommendations noted the attempt to implement plans and policies that would preserve society from the clutches of such crimes, such as the crime prevention and prevention policy, and others.